Modulation of glycinergic transmission in the rat spinal dorsal commissural nucleus by ginkgolide B - Nonaka, K.; Kondratskaya, E.; Maeda, M.; Yamaga, T.; Murayama, N.; Shin, M.-C.; Akaike, N. (Нейрофизиология, 2009)
The action of ginkgolide B (GB), the powerful compound of Ginkgo biloba extract, on glycinemediated spontaneous currents in rat spinal sacral dorsal commissural nucleus (SDCN) neurons was examined. IPSCs evoked in spinal cord slices were inhibited in a dose-dependent manner by the addition of GB to the superfusion solution. The amplitude of eIPSCs was reduced to 61 ± 6.4% by 10 μM GB, with acceleration of the kinetics of the currents indicating the effect of GB on channel pores. Both the amplitude and success ratio (Rsuc) of eIPSC induced by electrical focal stimulation of single glycinergic nerve endings (boutons) also decreased in the presence of 1 μM GB. These data suggest that GB modulates not only post-synaptic glycine receptors but also the pre-synaptic glycine release mac hinery.